Beyond terrorism: the development of the Australian security state - Hocking, Jenny (Allen & Unwin, 1993)
Verlagsinfo: This is the first account of the development and current powers of the shadowy organizations charged with the task of protecting us from "terrorists". It defines the orthodox theories anbd characterizations of terrorism such as perceived threat, and analyzes counter-terrorist measures bringing together state police special branches, federal security organizations such as ASIO and the Australian Protection Force (federal police), and the Army. The book details the history of terrorism in Australia from Croatian Separatists to Ananda Marga, the Family Court bombings and other incidents of political violence. It analyzes the military response to the Hilton bombing, placing it within a political and constitutional framework, and discusses crisis management and the relations between the media, law enforcement and intelligence organizations. "Beyond Terrorism" explores the development of Australia's internal security arrangements: the history of the political pressure to establish ASIO, the ramifications of the ASIO Act 1956 and the implications of the 1979 update of the Act. Jennifer Hocking's detailed and impeccably researched account of terrorism and the measures taken to counter it is an important and thought-provoking contribution to Australia's security debate.